A comprehensive analysis of lending patterns at Pawnshops in Java (Indonesia), 1926–1932 - W. Wisnu; N. Nawiyanto; W. Wasino; Muhammad Turhan Yani (Cogent Arts & Humanities)
This research states that there is a process of involvement of colonial debt in Java, Indonesia in the typical economic characteristics of the loan and repayment cycle in the pawnshop system which is related to Eid al-Fitr, the Javanese months, and the climate of the planting season. This characteristic becomes an interesting study and very valuable knowledge for the development of socio-economic history in the area studied. The ability to understand the socio-economic conditions of society needs to be carried out in line with government programs to alleviate poverty. Therefore, understanding this article will help the government and society in choosing alternative solutions to their economic problems. This study focuses on the relationship between the lending cycle during Eid and the tendency to borrow during the planting climate. This research uses qualitative historical research methods. The practice of providing credit services using the pawnshop model was carried out based on the rules set by the colonial government. The process of borrowing and repaying loan funds is explained with the power of various analytical approaches. This problem will be explained using historical studies and other social sciences to enrich the explanation.